COMMcast: Producing podcasts for communication theory. Issue 4 (1st October 2020) - Taylor, Julie L.; Blevins, Maria
Abstract : Students are often inseparable from Internet and streaming services through various technologies. This reality invites instructors to think about nuanced ways of employing technologies to engage students through both consumption and production of media in classrooms. Our assignment uses the modality of podcasts to encourage critical thinking and theoretical application. Student groups are tasked with producing informative podcast episodes on communication theories learned in class. Importantly, this assignment is a great way for students to adopt a strategy for lifelong learning with an introduction to podcasts, and the practice of making theory more widely accessible. Furthermore, the narrative focus of podcast episodes enhances assimilation of course content in ways students had not previously exhibited in assessments. The podcast assignment functions as a formative assessment for students who are both creating the content and listening to the production. Courses : Communication Theory and other courses that engage communication theories. Objectives: By the end of creating the podcast, students will be able to: (1) define a communication theory/concept according to course readings and content; (2) analyze a communication theory by applying learned concepts; (3) co-produce knowledge with others; and (4) identify and apply necessary skills for a compelling presentation.